Understanding Mycobacterium abscessus pulmonary and disseminated disease - Layer, Emily L., author; Ordway, Diane, advisor; Orme, Ian, committee member; Chatterjee, Delphi, committee member; Kirby, Michael, committee member (Colorado State University. Libraries, 2017)
Mycobacterium abscessus is an emerging human pathogen which is difficult to treat and results in increased mortality. Moreover, the cause of increasing case rates and also the pathogenesis of M. abscessus are poorly understood. M. abscessus belongs to the family of nontuberculous mycobacteria (NTM) classified as members of the rapidly growing mycobacteria (RGM). These environmental pathogens are ubiquitous and found in shower heads, tap water, natural water sources, and soil. Humans contract pulmonary or disseminated infections with M. abscessus by breathing in the aerosolized bacteria or ingesting contaminated water. Immunocompromised individuals such as HIV or AIDS patients, are more susceptible to infection with M. abscessus as are those with cystic fibrosis, bronchiectasis, and individuals on tumor necrosis factor α (TNFα) inhibitors. Strangely, an increasing population of patients becoming infected with M. abscessus are immunocompetent, tall, slender, Caucasian, non-smoking women. To expand our understanding of M. abscessus pathogenesis we developed mouse models that maintain high levels of bacterial infection to study immune responses induced by clinical strains of M. abscessus. Our results support the hypothesis that this bacteria can only persist in our animal models that possess a deficiency in macrophages and T cell function. Clustered bacterial strains obtained from Cystic Fibrosis patients are more virulent than unclustered bacterial strains obtained from Cystic Fibrosis patients. Additionally, counts of viable mycobacterial colony forming units and histological analysis in (Severe Combined Immunodeficiency) SCID mice on a beige background infected with clustered versus unclustered M. abscessus strains which were isolated from Cystic Fibrosis patients also supported the increased virulence exhibited by the clustered strains. Lastly, we show that major human M. abscessus outbreak strains, when infecting IL-3, GM-CSF deficient mice on an IL-2, Rag2 deficient background (GM/Rag-dblKO mice), result in increased bacterial replication and organ pathology and impaired protective immunity against this pathogen.
Keywords: animal; mouse; nontuberculous; model; abscessus; mycobacteria